Pelagic fish spared from ocean catch by integrating Black Soldier Fly Larvae in U.S. aquaculture production - Moore, Evan; Liu, Xiangping; Drewery, Merritt L. (Frontiers in Sustainable Food Systems, 2024)
The sustainability challenges associated with utilizing forage fish sourced from ocean catch as fish meal and fish oil in the aquaculture industry has increased the demand for alternative feeds. Previous research indicates that Black Soldier Fly Larvae (BSFL; Hermetia illucens) can partially replace fish meal and/or fish oil in the diets of farmed aquaculture species without compromising fish growth or efficiency. The objective of our study was to identify the amount of pelagic fish from ocean catch that could be spared from fish meal and fish oil production by integrating BSFL in the diets of three aquaculture species, Atlantic Salmon (Salmo salar), Rainbow Trout (Oncorhynchus mykiss), and Whiteleg Shrimp (Litopenaeus vannamei) in the United States. Annual output for these aquaculture species was collected for 2017–2019. For each specie, we calculated the total metric tons (MT) of spared pelagic fish, by taxa, from fish meal and fish oil production based on total lifetime food intake and dietary replacement rates of fish meal and fish oil by BSFL as established in previous literature. At the highest level of dietary BSFL substitution for fish meal and/or fish oil that did not sacrifice performance of the three aquaculture species, 40,843 MT of pelagic fish could be spared from ocean catch in the U.S. per year. Therefore, integrating BSFL in the diets of aquaculture species could reduce the demand for pelagic fish sourced from ocean catch and positively contribute to the sustainability of aquaculture production.